Uji Mekanik Membran Kitosan Berbahan Dasar Cangkang Kepiting - Indah Lestari; Dwi Sabda Budi Prasetya; Dewi Pangga (Lensa: Jurnal Kependidikan Fisika, 2018)
[Title: The Effect of Thinking Aloud Pair Problem Solving Learning Model Toward Student Physics Science Learning Outcomes]. This study aims to test mechanical on membrane composite membrane based crab shell and poly vinly Acetat (PVA). A mechanical test was performed to test the young modulus of the membrane in maintaining pore size using the "Tensilon" machine. The results show that chitosan / Poly Vinly Acetate composite membrane with preparation of comparison 25% -75%, 50% -50% and 75% -25%. For sample 25% -75% experience drying process faster than other sample. On the mechanical test of chitosan membrane / Poly Vinly Acetat showed the biggest value that is equal to 9.84 Mpa on comparison preparation 50% -50%. 25% -75% and 75% -25% preparations decreased by 4.68 MPa and 1.37Mpa.